2012
DOI: 10.1190/geo2011-0466.1
|View full text |Cite
|
Sign up to set email alerts
|

3D constraints and finite-difference modeling of massive sulfide deposits: The Kristineberg seismic lines revisited, northern Sweden

Abstract: The Kristineberg mining area in the western part of the Skellefte ore district is the largest base metal producer in northern Sweden and currently the subject of extensive geophysical and geologic studies aimed at constructing 3D geologic models. Seismic reflection data form the backbone of the geologic modeling in the study area. A geologic cross section close to the Kristineberg mine was used to generate synthetic seismic data using acoustic and elastic finite-difference algorithms to provide further insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 40 publications
1
10
0
1
Order By: Relevance
“…Note that massive sulfides rich in pyrite (a noneconomic sulfide mineral) tend to have higher velocities (e.g., those reported from Lokken Verk in Norway), whereas massive sulfides rich in pyrrhotite (e.g., those reported from Kristineberg and Flin Flon in Sweden and Canada, respectively) tend to fall along the mixing lines between pure pyrrhotite and mafic host rocks (Figure 2). Case studies presented in this special section (e.g., Dehghannejad et al, 2012;Duff et al, 2012;Malehmir et al, 2012a; are consistent with this observation. Malehmir et al (2011) report that magnetite-rich (>40% Fe) iron deposits show a significant acoustic impedance contrast against almost all lithologies (see Figure 2).…”
Section: Seismic Techniques and Their Basissupporting
confidence: 78%
See 1 more Smart Citation
“…Note that massive sulfides rich in pyrite (a noneconomic sulfide mineral) tend to have higher velocities (e.g., those reported from Lokken Verk in Norway), whereas massive sulfides rich in pyrrhotite (e.g., those reported from Kristineberg and Flin Flon in Sweden and Canada, respectively) tend to fall along the mixing lines between pure pyrrhotite and mafic host rocks (Figure 2). Case studies presented in this special section (e.g., Dehghannejad et al, 2012;Duff et al, 2012;Malehmir et al, 2012a; are consistent with this observation. Malehmir et al (2011) report that magnetite-rich (>40% Fe) iron deposits show a significant acoustic impedance contrast against almost all lithologies (see Figure 2).…”
Section: Seismic Techniques and Their Basissupporting
confidence: 78%
“…Three-dimensional, and even 4D geologic modeling studies (e.g., Dehghannejad et al, 2012), based on regional and mining camp scales and, sometimes, mine scale information, will be very important in limiting exploration targets suitable for 3D surveys and/or downhole seismic studies. A complete and comprehensive data integration program combined with modeling will help to reduce speculative interpretation, especially at greater depths, and provide greater value to industry.…”
Section: Looking Ahead: Challenges and Futurementioning
confidence: 99%
“…They found that the ability to detect a clear signature of the ore was dependent on the mineralization type and the nature of the host rock. Dehghannejad et al (2012) carried out finite-difference elastic and acoustic modeling to better understand the observed reflections in a 2-D seismic survey in the Kristineberg mining area of Sweden. The synthetic data showed that processing artifacts produced steeply dipping events that could be confused with reflectors.…”
Section: Scattering Behaviormentioning
confidence: 99%
“…, , , , ; Malehmir and Bellefluer ; Dehghannejad et al . , ; Bellefleur, Malehmir, and Müller ; Juhojuntti et al . ; Kukkonen et al .…”
Section: Introductionunclassified